2014
DOI: 10.1111/1744-9987.12248
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐Monthly Administration of a Lower Dose of Epoetin Beta Pegol Can Maintain Adequate Hemoglobin Levels in Hemodialysis Patients

Abstract: Epoetin beta pegol is a continuous erythropoietin receptor activator (CERA) with a long half-life. Although CERA has been shown to maintain adequate hemoglobin (Hb) levels at prolonged dosing intervals, the optimal dosing schedule remains unclear. We therefore compared the efficacy of maintaining hemoglobin levels with administration of twice-monthly CERA (TWICE) versus once-monthly CERA (ONCE). Twenty hemodialysis patients receiving epoetin beta (EPO) were enrolled in this crossover study. Patients were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
5
2
Order By: Relevance
“… 13 , 22 CERAs were previously reported to suppress hepcidin levels, inducing the release of stored iron and effective erythropoiesis. 11 , 12 , 14 Unexpectedly, the changes in hepcidin levels did not differ between the QW and Q2W groups in the present study. Similarly, ferritin and TSAT levels did not change in the QW group.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“… 13 , 22 CERAs were previously reported to suppress hepcidin levels, inducing the release of stored iron and effective erythropoiesis. 11 , 12 , 14 Unexpectedly, the changes in hepcidin levels did not differ between the QW and Q2W groups in the present study. Similarly, ferritin and TSAT levels did not change in the QW group.…”
Section: Discussioncontrasting
confidence: 46%
“…Hepcidin regulates plasma iron levels by decreasing iron absorption and the release of recycled Hb iron and increasing intracellular iron stores 13,22 . CERAs were previously reported to suppress hepcidin levels, inducing the release of stored iron and effective erythropoiesis 11,12,14 . Unexpectedly, the changes in hepcidin levels did not differ between the QW and Q2W groups in the present study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…We also exclude other possible causes of anemia -deficiency of vitamin B12 or folic acid. We did not also assess erythropoietin levels and their relations to iron status as it was reported that hepcidin or prohepcidin were unaffected during therapy with erythropoiesis stimulating agents [36,37]. It appears that some novel biomarkers i.e.…”
Section: Discussionmentioning
confidence: 99%
“…administration [6], enabling reduction of CERA dose [7,8], improving iron use efficiency [7,9,10], and increasing erythropoiesis [6]. The guidelines on the management of renal anemia, published by the Japanese Society for Dialysis Therapy (JSDT) as the 2015 edition, suggest that CERA Q2W may be more effective than Q4W [11].…”
Section: Introductionmentioning
confidence: 99%